2019
DOI: 10.1038/s41598-019-46086-y
|View full text |Cite
|
Sign up to set email alerts
|

Differentiation of single lymphoma primary cells and normal B-cells based on their adhesion to mesenchymal stromal cells in optical tweezers

Abstract: We have adapted a non-invasive method based on optical tweezers technology to differentiate between the normal B-cells and the B-cell non-Hodgkin lymphoma (B-NHL) cells derived from clinical samples. Our approach bases on the nascent adhesion between an individual B-cell and a mesenchymal stromal cell. In this study, a single B-cell was trapped and optically seeded on a mesenchymal stromal cell and kept in a direct contact with it until a stable connection between the cells was formed in time scale. This appro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(23 citation statements)
references
References 72 publications
0
23
0
Order By: Relevance
“… 56 Several reports showed that stromal cells chemoprotect tumor cells through direct cell–cell contact; thus, there is an urgent need to develop models which allow studying such direct interactions. 19 Importantly, our group previously investigated the direct interactions between B-cell lymphoma and stromal cells in optical tweezers using a 2D culture, 57 , 58 whereas the 3D organization and cellular microenvironment emerged as critical determinants of lymphoma pathogenesis and drug resistance.…”
Section: Discussionmentioning
confidence: 99%
“… 56 Several reports showed that stromal cells chemoprotect tumor cells through direct cell–cell contact; thus, there is an urgent need to develop models which allow studying such direct interactions. 19 Importantly, our group previously investigated the direct interactions between B-cell lymphoma and stromal cells in optical tweezers using a 2D culture, 57 , 58 whereas the 3D organization and cellular microenvironment emerged as critical determinants of lymphoma pathogenesis and drug resistance.…”
Section: Discussionmentioning
confidence: 99%
“…This limitation was overcome by the transition to infrared lasers, which enabled longer manipulation times of living cells, resulting in the broader use of optical tweezers in cell research [43]. In our previous works, we investigated the effect of a low-intensity optical laser on living lymphoma cells [7,8,22]. We proved that laser operation at 1064 nm poses a low risk of optical damage to lymphoma cells.…”
Section: Discussionmentioning
confidence: 99%
“…The precise measurements of the adhesion force, as well as the influence of the laser beam used on living cell viability, have been described in our earlier papers [7,8]. All experiments were carried out at room temperature, i.e., 25 • C. The spheroids formed in the OT were then transferred to an incubator and cultured in a hanging drop in RPMI-1640 (Gibco, Paisley, UK) with 10% bovine serum (Gibco, Paisley, UK) and antibiotics (Sigma-Aldrich Chemie GmbH) under standard conditions.…”
Section: Formation Of Multicellular Hybrid Spheroids In Optical Tweezersmentioning
confidence: 99%
See 2 more Smart Citations